A panel of human neutralizing mAbs targeting SARS-CoV-2 spike at multiple epitopes (2020)
The novel highly transmissible human coronavirus SARS-CoV-2 is the causative agent of the COVID-19 pandemic. Thus far, there is no approved therapeutic drug specifically targeting this emerging virus. Here we report the isolation and characterization of a panel of human neutralizing monoclonal antibodies targeting the SARS-CoV-2 receptor binding domain (RBD). These antibodies were selected from a phage display library constructed using peripheral circulatory lymphocytes collected from patients at the acute phase of the disease. These neutralizing antibodies are shown to recognize distinct epitopes on the viral spike RBD. A subset of the antibodies exert their inhibitory activity by abrogating binding of the RBD to the human ACE2 receptor. The human monoclonal antibodies described here represent a promising basis for the design of efficient combined post-exposure therapy for SARS-CoV-2 infection.